Արիստակես Լաստիվերցու Պատմության հավանական պատվիրատուն - Եղիազարյան, Վանո (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
1. «История» Аристакеса Ластиверци, как и «Истории» его предшественников и последователей, имеет заказчика, так как наличие меценатазаказчика является устойчивой и повторяемой жанровой особенностью историографической прозы. 2. Симпатии автора в «Истории» на стороне Багратидов. 3. Перевод выражения «վասն որոյ պատմութիւնս է» – «о ком эта история» – во второй главе «Истории» является неубедительным, поскольку в «Истории» Аристакеса повествуется не о царе Гагике I. 4. Учитывая древнеармянские семантические нюансы слова «վասն» (основное значение: «о»), мы отдали предпочтение другим вариантам перевода: «благодаря кому эта история», «для кого эта история», «посредством кого эта история», «при чьем посредничестве эта история». Во всех этих случаях вероятным автором «Истории» можно считать царя Гагика I Багратуни. 5. Царь Гагик заказал Аристакесу написать «Историю», но в скором времени скончался. Тем не менее автор продолжил начатую работу, изложив те исторические события, которые он считал важными. 1. The “History” by Aristakes Lastiversi, like the “Histories” of his predecessors and successors, had a promoter, since the presence of a patron-promoter was a stable and repeatable genre feature of historiographical prose. 2. In the “History”, the author’s sympathy was with the Bagratuni dynasty. 3. The translation of the expression «վասն որոյ պատմությունս է» – “who is this story about” – in the second chapter of the “History” is unconvincing, since the “History” of Aristakes does not tell about King Gagik I. 4. Taking into account the ancient Armenian semantic nuances of the word «վասն» (the main meaning: “about”), we prefer other translation options: “thanks to whom this story is”, “for whom this story is”, “through whom this story is”, “through whose mediation this story is”. In all these cases, King Gagik I Bagratuni could be considered the probable promoter of the “History”. 5. King Gagik I ordered Aristakes Lastivertsi to write the “History”', but soon passed away. Nevertheless, the author continued the work he had begun, outlining those historical events that he considered important.
Keywords: Քննարկումներ; Պատմություն